Urbane Realitäten : Fokus Istanbul - Martin-Gropius-Bau, berlin (Berlin : Künstlerhaus Bethanien Berlin, 2005)
Akdogan, Rey ; Aladag, Nevin ; Bijl, Marc ; Bock, Katinka ; Boyadjiev, Luchezar ; Bratkov, Sergey ; Bryce, Fernando ; Chalayan, Hussein ; Chong, Heman ; Garenne, Christine de la ; Der-Meguerditchian, Silvina ; Deroubaix, Damien ; Erek, Cevdet ; Friedl, Peter ; Galentz, Archie ; Gediz, Leyla ; Güler, Ara ; Haaning, Jens ; Havekost, Eberhard ; Henriksson, Minna L. ; Hoeck, Richard ; Holzapfel, Olaf ; Hornemann, Thomas ; Istanbul Palimpsest ; Kepenek, Ali ; Kim, Lina ; Köbberling, Folke ; Kaltwasser, Martin ; Köksal, Serhat ; Koh, Germaine ; Komoroczki, Tamas ; Németh, Hajnal ; Koshlyakov, Valery ; Lenglet, Lucas ; Lewandowsky, Via ; Metzel, Olaf ; Ozkaya, Serkan ; Oroschakoff, Haralampi G. ; Pérez Agirregoikoa, Juan ; Ramberg, Lars ; Reynolds, Reynold ; Romo, Sebastian ; Sarkis ; Scheipner, Robert ; Schleime, Cornelia ; Shawky, Wael ; Stangl, Reinhard ; Stratmann, Roland ; Strauss, Joulia ; Sungu, Asli ; Thome, Bernhard ; Tsantila, Evanthia ; Tur, Nasan ; Vardaman, Sencer ; Vece, Costa ; Weber, Suse ; Weiss Leder, Ute ; Welz, Peter ; Wesely, Michael ; Winkler, HS ; Wudke, Ina
Exhibition in Martin-Gropius-Bau, Berlin, 09.07.2005 - 03.10.2005
Duits
Engels
Turks
boek